MODEL PENGEMBANGAN EKONOMI DAERAH PESISIR DAN PULAU-PULAU KECIL MELALUI PENDEKATAN INTEGRASI MARINE-TOURISM INDUSTRY DI DESA BARU DAN BUKU LIMAU KECAMATAN MANGGAR KABUPATEN BELITUNG TIMUR - Reniati Reniati; Fadillah Sabri; Wahyu Adi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2014)
The objectives of the KKN-PPM program can be divided into three: Community Empowerment, enhancing the role of Higher Education and providing support for Local Government. These activities are in order to solve the issues faced by coastal areas and small islands (WP3K), namely: Not optimal spatial planning and utilization in WP3K, low quality of human resources in WP3K management, limited facilities and infrastructure, not optimal empowerment of coastal resources for economic development, not optimal management of fisheries potential, not optimal development of potential and marine tourism objects, as well as pollution and environmental damage. The activities carried out to solve the problems faced by coastal areas and small islands (WP3K) include making a Master Plan for